“ONE NATION HEALTHY NATION” A STUDY ON PROTECTING HEALTH CARE FINANCING OF POOR AND RURAL HOUSEHOLDS UNDER MISSION ’VIKSIT BHARAT @2047 - Rath, Jyoti Prakash; Jain, Nisha (International Journal of Research -GRANTHAALAYAH, 2025)
Health Care can be seen as an important aspect in the mission of Viksit Bharat. It is the responsibility of Government both at States and Centre to provide adequate health care facilities to the citizens of the nation. Growing rate of heath care services in last few years has raised the alarm even. Mission Viksit Bharat will certainly be accomplished with developed health care mechanism and facilities in the country. Central government of India has taken number of initiatives in the form of government sponsored health insurance schemes in last few years to protect the health care financing proposition of poor and rural households residing at different places in the country. This study is made to evaluate the contribution of Central Government of India towards protecting health care financing needs of poor and rural households in the country through government sponsored schemes. Data used in this research are generally collected from secondary sources i.e. Government Reports, Websites, Magazines, Journals and several other literatures available and accessible. There are different schemes issued for the general public as a protection shield against high health care expenditures such as ESI Scheme, CGH Scheme and Ayushman Bharat (includes both RSBY and PMJAY) by the central government. These schemes help the beneficiaries in availing medical treatment and other health care benefits from government and private hospitals without having the hardship of financing the same out of pocket. India is a country with more than 150 crores of population with a large number of poor and vulnerable families. Central Government are required to put in aggressive strategies towards revamping health care system prevailing in the country and to infuse more funds in health insurance schemes in years to come. This may certainly be helpful in reaching the goal of Viksit Bharat within the time frame providing all needed health care facilities to the citizens of our country.